PEMANFAATAN KECERDASAN BUATAN DALAM PENYUSUNAN MATERI PENDIDIKAN AGAMA ISLAM DI SMK NEGERI 1 BELITANG MADANG RAYA: PELUANG DAN TANTANGAN - Widiana; Marlina; Ikhsanudin, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The development of Artificial Intelligence (AI) has influenced the educational sector, including Islamic Religious Education (PAI). This study aims to analyze the utilization of Artificial Intelligence in preparing Islamic Religious Education learning materials at SMK Negeri 1 Belitang Madang Raya and to identify the opportunities and challenges faced by teachers. This research employed a qualitative approach with a case study design involving four Islamic Religious Education teachers as research subjects. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results showed that teachers utilized Artificial Intelligence to search for references, summarize materials, prepare learning content, and develop evaluation questions. The use of Artificial Intelligence increased efficiency, facilitated access to learning resources, and supported innovative learning. However, challenges such as information validity, limited digital literacy, internet accessibility, and dependence on technology were also identified. Therefore, teachers still play an important role in validating learning materials to ensure their compatibility with Islamic values and educational objectives.